Carrying Capacity for Land Rehabilitation Strategy in Merawu Watershed, Banjarnegara District - Marcella, P. (IOP Publishing, 2022)
The upstream watershed area (DAS) has a function as a buffer zone. The Merawu watershed is one of the upstream parts of the Serayu watershed which is dominated by agricultural land. The declining carrying capacity of the Merawu watershed is indicated by the imbalance between supply and demand for resources in the Merawu watershed. For a long time, it can interfere with the function of the soil as life support. The research objectives are: 1) analyzing the carrying capacity of the Merawu watershed through 3 approaches, namely: ecological footprint (land capacity), water capacity,, and land protection capacity. The research method used is to compare supply and demand. And 2) Formulating a recovery strategy in the Merawu watershed based on an analysis of the environmental carrying capacity and focusing on increasing the carrying capacity. The results showed that the Merawu watershed has the carrying capacity of the protection function in the overshoot condition, the water carrying capacity in the conditionallysave condition, and the carrying capacity of the land in the overshoot condition. There are five watershed recovery strategies in the upstream, middle and downstream areas to increase carrying capacity.